2016
DOI: 10.1002/jor.23492
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of total knee arthroplasty in 5° or 7° valgus: A study of gap imbalances and changes in limb and knee alignments from native

Abstract: This study calculated the frequency of occurrence of gap imbalances between medial and lateral compartments at 0° flexion and within a compartment between 0° and 90° flexion, and changes in limb and knee alignment from native after computer simulation of total knee arthroplasty (TKA) with the knee set in 5° or 7° valgus at 0° flexion. TKA was simulated on 49 3D bone models of native limbs. At 0° flexion, the femoral component was set in 5° or 7° valgus from the anatomic axis of the femur, and the tibial compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Finally, a single method for setting the rotation of the femoral component was studied with MA whereas multiple methods are used clinically. 12,27…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a single method for setting the rotation of the femoral component was studied with MA whereas multiple methods are used clinically. 12,27…”
Section: Discussionmentioning
confidence: 99%
“…Related to the second key finding, the result that only 6 of 20 neutral positions were statistically different from native after KA TKA has several clinical implications. No statistical differences of the V‐V neutral positions indicate that KA TKA likely achieved the goal of aligning the femoral and tibial components to restore the native joint lines and thus the native alignments of the limb and knee because malalignments would cause differences in the V‐V neutral position . No statistical differences of the C‐D neutral position indicate that the correct tibial insert thickness was selected, and that the posterior tibial slope was correctly set using the intraoperative quality assurance checks .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was reported that TKA using MA required the management of complex and uncorrectable collateral ligament imbalance, and it led to a wide range of changes in tibiofemoral alignment from normal knee conditions. 43,44 KA TKA has the advantage of preventing imbalance of the collateral ligaments, which have a wide variety of complex mechanisms that are not correctable through collateral ligament release, as well as a wide range of changes in the natural alignment of the lower extremity resulting from MA TKA. KA TKA restores the normal alignment of the lower extremity and the joint line of the knee, thus providing more physiological forces exerted on the collateral ligaments than MA TKA, which is unnaturally aligned to a neutral MA.…”
Section: Discussionmentioning
confidence: 99%